2016
DOI: 10.7717/peerj.2735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid supplementation in maturation diet on female reproductive performance and larval quality of giant river prawn (Macrobrachium rosenbergii)

Abstract: The giant river prawn (Macrobrachium rosenbergii) is one of the most farmed freshwater crustaceans in the world. Its global production has been stalling in the past decade due to the inconsistent quality of broodstock and hatchery-produced seeds. A better understanding of the role of nutrition in maturation diets will help overcome some of the production challenges. Arachidonic acid (20:4 n-6, ARA) is a fatty acid precursor of signaling molecules important for crustacean reproduction, prostaglandins E and F of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
1
11
0
4
Order By: Relevance
“…Injection of arachidonic acid significantly induces maturation, in shrimp to Penaeus semisulcatus at a dose of 5 μg/g body weight and 10 μg/g body weights [35]. Earlier it was reported that arachidonic acid supplementation through diet significantly promotes reproductive performance in tank domesticated Penaeus monodon [36], in Daphnia magna [37] and improved gonad somatic index, hepatosomatic index, egg clutch weight and fecundity in prawn, Macrobrachium rosenbergii [38]. In several fishes, also Arachidonic acid supplementation increases reproduction [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Injection of arachidonic acid significantly induces maturation, in shrimp to Penaeus semisulcatus at a dose of 5 μg/g body weight and 10 μg/g body weights [35]. Earlier it was reported that arachidonic acid supplementation through diet significantly promotes reproductive performance in tank domesticated Penaeus monodon [36], in Daphnia magna [37] and improved gonad somatic index, hepatosomatic index, egg clutch weight and fecundity in prawn, Macrobrachium rosenbergii [38]. In several fishes, also Arachidonic acid supplementation increases reproduction [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Only the hepatopancreas of females in the final stage (V) in both phenotypes showed a significant decrease in water content. This is associated with increased lipid accumulation in this organ during stage V (final stage), which constitutes the final energy reserve for ovary maturation (Haefner & Spaargaren, ; Kangpanich et al, ; Soonklang et al, ; Spaargaren & Haefner, ). Franceschini‐Vicentini et al () and Ribeiro, Papa, Vicentini, and Franceschini‐Vicentini (), when analysing the histological and ultrastructural aspects of the hepatopancreatic tubules of M. amazonicum , identified five epithelial cell types: E (embryonic), F (fibrillar), B (blister‐like), R (resorptive) and M (midget) cells.…”
Section: Discussionmentioning
confidence: 99%
“…After the identification of the prawns according to Pillegi (), female carapace length (CL—distance between the posterior margin of the ocular orbit and the mid‐point of the posterior margin of the carapace) was measured with an analogic caliper (0.02 mm) and the ovarian stage was initially assessed by the colour and size of the ovary observed through the exoskeleton (Chang & Shih, ; Kangpanich et al, ). Immediately after these procedures, all animals were dissected and analysed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations